Penerapan Metode Additive Ratio Assessment (ARAS) dalam Pemilihan Komandan Regu Security Terbaik pada PT. Pelindo Daya Sejahtera (PDS) (International Forum of Researchers and Lecturers, 2024)
This research discusses the problem of optimizing the selection of security team commanders at PT. Pelindo Daya Sejahtera (PDS) to increase operational effectiveness. The aim of the research is to develop a Decision Support System (DSS) using the Additive Ratio Assessment (ARAS) method to select the best candidate to become the best security team commander. The data used includes alternative data as well as criteria such as work experience, leadership skills and technical security knowledge. The ARAS method allows the assessment of candidates based on scores that reflect their performance against established criteria. The result is a rating, which helps management select the most suitable commander based on the rating.